Removal/recovery of acetic acid from waste water by adsorption on bagasse and coconut jute carbon - Chand, Shri; Vivek Kumar; Majumdar, C.B. (1999)
Removal of acetic acid from waste water has been investigated using adsorbents based on bagasses and co-conut jute. The effects of acetic acid concentration, adsorbent dosage, contact time and temperature were studied in batch experiment. The removal is most effective with activated bagasse carbon. A maximum removal of around 51% was achieved under the conditions of the experiments. The data fit well in the Freundlich isotherm. - Reproduced
Keywords: Water; Acids; Waste water